2015
DOI: 10.1530/eje-15-0284
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery disease risk among obese metabolically healthy young men

Abstract: Objective: The aim of this study was to assess coronary artery disease (CAD) risk among obese young men without metabolic risk factors. Design: A longitudinal study in a historical cohort. Methods: Incident CAD during a median follow-up of 6.1 years was assessed among 31 684 young men (mean age 31.2G5.7 years) of the Metabolic, Lifestyle and Nutrition Assessment in Young Adults (MELANY) cohort. Participants were categorized by BMI and the number of metabolic abnormalities (based on the Adult Treatment Panel-II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…25,27,32 Two studies reported data for female participants, 35,36 and three reported data for male subjects only. 15,37,38 Participants were from diverse geographical locations: 11 studies were from Europe, 7,16,[20][21][22]25,[30][31][32][33]38 six from North America, 15,24,28,[34][35][36] three from the Middle East, 23,29,37 two from Asia 26,27 and one from Oceania (Australia). 6 No studies detailed the ethnic origins of their subjects.…”
Section: Discussionmentioning
confidence: 99%
“…25,27,32 Two studies reported data for female participants, 35,36 and three reported data for male subjects only. 15,37,38 Participants were from diverse geographical locations: 11 studies were from Europe, 7,16,[20][21][22]25,[30][31][32][33]38 six from North America, 15,24,28,[34][35][36] three from the Middle East, 23,29,37 two from Asia 26,27 and one from Oceania (Australia). 6 No studies detailed the ethnic origins of their subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Between January 1967 to December 31, 2010, in total, 2,454,693 adolescents were evaluated, irrespective of whether they actually served in the military, as recently described. 20 After excluding 64,186 individuals who were missing height or weight data and 82,377 non-Jewish examinees (because of the nonrepresentativeness of their source populations), 2,298,130 participants remained. We then excluded 503,560 individuals who were evaluated after December 2002 and did not have the opportunity for at least 10 years of follow-up.…”
Section: Study Populationmentioning
confidence: 99%
“…This study also revealed that in young patients 30-40 years old, obesity and hyperlipidemia were the major predictors in this group of patients [17]. In a study made to assess the risk of CAD in patients who are obese but free of metabolic risk factors, it was found that although patients are only obese the progression of obesity may contribute to amplified risk for incidental CAD especially in young men [18].…”
Section: Discussionmentioning
confidence: 73%